2020
DOI: 10.1186/s12870-020-02657-0
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of a candidate gene for cool-temperature-induced albinism in ornamental kale

Abstract: Background The symptoms of cool-temperature-induced chlorosis (CTIC) are widely existed in higher plants. Although many studies have shown that the genetic mechanism of CTIC is generally controlled by recessive genes in model plants, the dominant inheritance of albinism has not been reported thus far. Here, two CTIC mutants, Red Kamome and White Kamome, were utilized to analyse the inheritance of the albino trait in ornamental kale. The objective of this investigation is to fine-map the target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Abnormal chloroplast development is a major reason for the formation of chlorophyll-deficient mutants ( Zhang et al, 2020 ). Previous studies have shown that the white leaf of ornamental kale formation was mainly due to chloroplast deficiency ( Zhou et al, 2013 ; Yan et al, 2020 ). Chloroplast biogenesis involved several functional processes including thylakoid formation, pigment synthesis, plastid divisions, retrograde signaling, etc.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Abnormal chloroplast development is a major reason for the formation of chlorophyll-deficient mutants ( Zhang et al, 2020 ). Previous studies have shown that the white leaf of ornamental kale formation was mainly due to chloroplast deficiency ( Zhou et al, 2013 ; Yan et al, 2020 ). Chloroplast biogenesis involved several functional processes including thylakoid formation, pigment synthesis, plastid divisions, retrograde signaling, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms of white leaf formation are complex and related to multiple biochemical processes and genes in different ornamental kale cultivars. Yan et al (2020) identified the cytochrome P450 gene ( Bol015404 ) as the most likely candidate gene for white leaf formation of ornamental kale by using BSR-seq. In this study, this gene was a significantly high expression in white leaf tissue than that in the green leaf tissue [log 2 (W/G) = 12.071, log 2 (W1/G2) = 1.322].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the two parental lines were subjected to resequencing with 30 × depth. As previously described (Yan et al, 2020 ), BSA-seq analysis was performed using a user-friendly script. The clean reads from two pools were aligned against the long-read reference genome “QZ-16” (ENA number: PRJEB37015) by Bowtie (Langmead and Salzberg, 2012 ).…”
Section: Methodsmentioning
confidence: 99%